2019
DOI: 10.1088/2515-7647/ab281a
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for the monitoring and process control of femtosecond laser machining

Abstract: Whilst advances in lasers now allow the processing of practically any material, further optimisation in precision and efficiency is highly desirable, in particular via the development of real-time detection and feedback systems. Here, we demonstrate the application of neural networks for system monitoring via visual observation of the work-piece during laser processing. Specifically, we show quantification of unintended laser beam modifications, namely translation and rotation, along with real-time closed-loop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…This work was enhanced by McDonnell et al [196], who extended it to include three laser pulses and showed that the cGAN was able to predict that multiple pulses could enable a higher machining resolution than a single laser pulse when each pulse had a specific spatialintensity profile. In combining the concepts of real-time correction and DMD-based beam shaping, Xie et al [197] showed that a DMD can be used in a real-time feedback loop to provide corrections to the beam shape and position during laser machining, along with the demonstration of the real-time ceasing of laser machining at task completion, despite not knowing the task length beforehand. As presented here, recent results have demonstrated the potential for using ANNs to model thermal and structural effects during laser machining [198,199] and using cGANs for 3-D visualisation of surfaces, such as those produced for single [98] and multiple laser pulses [196].…”
Section: Deep Learningmentioning
confidence: 99%
“…This work was enhanced by McDonnell et al [196], who extended it to include three laser pulses and showed that the cGAN was able to predict that multiple pulses could enable a higher machining resolution than a single laser pulse when each pulse had a specific spatialintensity profile. In combining the concepts of real-time correction and DMD-based beam shaping, Xie et al [197] showed that a DMD can be used in a real-time feedback loop to provide corrections to the beam shape and position during laser machining, along with the demonstration of the real-time ceasing of laser machining at task completion, despite not knowing the task length beforehand. As presented here, recent results have demonstrated the potential for using ANNs to model thermal and structural effects during laser machining [198,199] and using cGANs for 3-D visualisation of surfaces, such as those produced for single [98] and multiple laser pulses [196].…”
Section: Deep Learningmentioning
confidence: 99%
“…In this manuscript, a novel laser material removal patterning process, actuated by reinforcement learning-controlled XYZ stages, is demonstrated, aiming to provide automatic path-planning and a self-correction ability to the patterning process. This work builds upon previous work by the authors that showed the capability of reinforcement learning (RL) for automated movement of small particles through a maze via the laser tweezers effect [1], and for deep learning for controlling the number of pulses used for machining through a thin film [2]. Here the application of reinforcement learning for experimental control of the spatial positions of laser pulses during laser machining is presented.…”
mentioning
confidence: 83%
“…This strategy has been shown to be effective in modelling laser machining [24][25][26][27][28][29], and it is significantly faster in terms of computational speed. Different ML methods have been demonstrated to be able to model physical phenomena directly from experimental data without considering any underlying physical equations [10,27,30]. For instance, Mc-Donnell et al [16] applied ML techniques to grey cast iron and studied the height of the laser produced crown and dimple depth as a function of the laser pulse energy, its repetition rate and the number of pulses.…”
Section: Introductionmentioning
confidence: 99%